2022
DOI: 10.3390/ijms24010664
|View full text |Cite
|
Sign up to set email alerts
|

Oxidative Stress Response’s Kinetics after 60 Minutes at Different (30% or 100%) Normobaric Hyperoxia Exposures

Abstract: Oxygen is a powerful trigger for cellular reactions and is used in many pathologies, including oxidative stress. However, the effects of oxygen over time and at different partial pressures remain poorly understood. In this study, the metabolic responses of normobaric oxygen intake for 1 h to mild (30%) and high (100%) inspired fractions were investigated. Fourteen healthy non-smoking subjects (7 males and 7 females; age: 29.9 ± 11.1 years, height: 168.2 ± 9.37 cm; weight: 64.4 ± 12.3 kg; BMI: 22.7 ± 4.1) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
18
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 17 publications
(18 citation statements)
references
References 56 publications
0
18
0
Order By: Relevance
“…Reactive O 2 species are also produced throughout normal metabolic reactions, including anaerobic respiration at the electron transport chain within the mitochondria, as well as reactions of cyclooxygenases, lipoxygenases, peroxidases, and cytochrome P450 enzymes ( Kirsch and de Groot, 2000 ). Nevertheless, the high O 2 concentration disrupts the pro-oxidant-antioxidant balance, leading to general oxidative damage of DNA, lipids and proteins ( Ottolenghi et al, 2020 ; Juan et al, 2021 ; Leveque et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Reactive O 2 species are also produced throughout normal metabolic reactions, including anaerobic respiration at the electron transport chain within the mitochondria, as well as reactions of cyclooxygenases, lipoxygenases, peroxidases, and cytochrome P450 enzymes ( Kirsch and de Groot, 2000 ). Nevertheless, the high O 2 concentration disrupts the pro-oxidant-antioxidant balance, leading to general oxidative damage of DNA, lipids and proteins ( Ottolenghi et al, 2020 ; Juan et al, 2021 ; Leveque et al, 2023 ).…”
Section: Discussionmentioning
confidence: 99%
“…Hyperoxia at a FiO 2 of 60% was shown to cause significant oxidative damage to hippocampal lipids and proteins after 2 h of oxygenation, but not at a FiO 2 of 40% ( Machado et al, 2022 ). Furthermore, in a study of human subjects, researchers found that the levels of oxidation markers were increased in the first 8 h after exposure to 1 h normobar hyperoxia (30% and 100%), and the subsequent inflammatory response was significantly higher at FiO 2 of 100% ( Leveque et al, 2023 ). In our study, we hypothesized that the difference between the hippocampal regions observed at 30% and 100% O 2 concentrations may arise from cell type-specific differences in terms of sensitivity to ROS.…”
Section: Discussionmentioning
confidence: 99%
“…More research needs to be conducted to determine the best method of administration, as well as to optimize the dose, frequency, and duration of H 2 therapy. This may also include changing partial pressures (concentrations) of oxygen gas, which can create meaningful biphasic responses in ROS production and inflammatory signaling [56].…”
Section: Discussionmentioning
confidence: 99%
“…Given their strong ability to react chemically with their environment, ROS are well known to lead to several pathological consequences [ 34 ]. Surprisingly, depending on the specific context, ROS can exhibit both protective and deleterious effects on the organism, with the same molecule exerting opposing effects on biological processes [ 35 ]. The impact of these effects relies on the interplay between the production of ROS and their clearance rates, wherein antioxidants and scavengers assume a critical role [ 36 ].…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%
“…Lastly, the production rates of ROS and antioxidants vary according to different oxygenation levels, each following unique kinetic patterns [ 35 , 47 ]. Therefore, it is conceivable to assume that the vasoactive activity of ROS, as well as RNS and antioxidants, may depend not only on the types of ROS and their concentration, but also on a third feature, i.e., the kinetics of their production and degradation.…”
Section: Reactive Oxygen Speciesmentioning
confidence: 99%